ANALISIS PREFERENSI MASYARAKAT TERHADAP JASA TRANSPORTASI BUS TRANS PADANG - Novira Arnita Riska Putri; Zul Azhar (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to determine the extent of the influence of respondents'income, the existence of online motorcycle taxis and accessibility to people'spreferences for Trans Padang Bus transportation services. The data in this study used a primer that was taken in October 2021. The data a collection technique was by distributing questionnaires and conducting direct observations. The population in this study was all users of Trans Padang Bus transportation services, by taking a sample of 100 respondents. This study uses a multiple regression analysis with the Ordinary Least Square method. For the questions in the questionnaire, a validity and reliability tests were carried out. The results of this study indicate that partially (1) respondents' income has a positive and significant effect on people's preferences for Trans Padang Bus transportation services. (2) the existence of an online motorcycle taxis has a significant and significant effect on people's preferences for Trans Padang Bus transportation services. (3) the trans Padang Bus accessibility has a positive and significant effect on Trans Padang Bus transportation services.